Mother's Behavior Regarding Preparation of Healthy Breakfast and Snacks for Children: A School-based Intervention Research - Sakineh Rakhshanderou; Mohtasham Ghaffari; Ameneh Pooresmaeil Dorosteh (Iranian Journal of Health, Safety and Environment, 2022)
Healthy breakfast and snacks play an important role in students' physical and mental health and education is one of the most effective strategies for improving the nutritional status of children. The aim of this study was to survey the effect of school-based educational intervention on mothers' behavior with respect to healthy breakfast and snacks for children. In this experimental study, random sampling was conducted and 120 students were selected and divided into two experimental and control groups and their mothers were invited to participate in the study. Samples were examined in two stages through pre-test, and a delayed post-test with a questionnaire that consists of demographic information questions related to knowledge, attitude, perceived benefits, perceived barriers and behavior. Training, lectures and group discussion methods and question and answer with educational aids such as pamphlets were used. Data were analyzed by using SPSS16 and paired t-test, t-test and chi-square analyses were employed. The mean scores of knowledge (6.20±88.30), attitude (1.65±25.95) and perceived benefits (0.29 ±17.95), perceived barriers (2.71±34.70), and behavior of mothers (8.38± 115) in the experimental group significantly increased after intervention (P